Household costs of hospitalized dengue illness in semi-rural Thailand - Tozan, Yeşim; Ratanawong, Pitcha; Wilder-Smith, Annelies (PLoS neglected tropical diseases, 2017)
Background: Dengue-related illness is a leading cause of hospitalization and death in Thailand and other Southeast Asian countries, imposing a major economic burden on households, health systems, and governments. This study aims to assess the economic impact of hospitalized dengue cases on households in Chachoengsao province in eastern Thailand. Methods: We conducted a prospective cost-of-illness study of hospitalized pediatric and adult dengue patients at three public hospitals. We examined all hospitalized dengue cases regardless of disease severity. Patients or their legal guardians were interviewed using a standard questionnaire to determine household-level medical and non-medical expenditures and income losses during the illness episode. Results: Between March and September 2015, we recruited a total of 224 hospitalized patients (<5 years, 4%; 5-14 years, 20%, 15-24 years, 36%, 25-34 years, 15%; 35-44 years, 10%; 45+ years, 12%), who were clinically diagnosed with dengue. The total cost of a hospitalized dengue case was higher for adult patients than pediatric patients, and was US-Dollar 153.6 and US-Dollar 166.3 for pediatric DF and DHF patients, respectively, and US-Dollar 171.2 and US-Dollar 226.1 for adult DF and DHF patients, respectively. The financial burden on households increased with the severity of dengue illness. Conclusions: Although 74% of the households reported that the patient received free medical care, hospitalized dengue illness cost approximately 19-23% of the monthly household income. These results indicated that dengue imposed a substantial financial burden on households in Thailand where a great majority of the population was covered by the Universal Coverage Scheme for health care.